2018
DOI: 10.1016/j.bbrc.2018.09.168
|View full text |Cite
|
Sign up to set email alerts
|

Both the N- and C- terminal regions of the Chlamydial inclusion protein D (IncD) are required for interaction with the pleckstrin homology domain of the ceramide transport protein CERT

Abstract: An obligate intracellular bacterium Chlamydia trachomatis requires host lipid ceramide for their replication within an intracellular membranous compartment, the inclusion. Chlamydial inclusion membrane protein D (IncD) composed of two closely linked long hydrophobic domains with their N- and C-termini exposed to the host cytosol, binds directly to the pleckstrin homology (PH) domain of the ceramide transport protein (CERT), likely redirecting ceramide to the inclusion. The precise regions of IncD required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Moreover, the C. trachomatis inclusion membrane protein IncD specifically interacts with the PH (pleckstrin homology) domain of CERT, suggesting that IncD is involved in the recruitment of CERT to C. trachomatis inclusions. Co-transfection studies together with phylogenetic analysis revealed that both the N- and C-terminal regions of IncD are required for binding to the CERT PH domain, allowing C. trachomatis to redirect host cell-derived ceramides to inclusions more efficiently ( Kumagai et al, 2018 ). In cells depleted of CERT ( via short interfering RNAs and siRNAs), CERT was no longer detected on the surfaces of C. trachomatis inclusions, which resulted in smaller inclusions than cells treated with control siRNAs ( Derre et al, 2011 ; Elwell et al, 2011 ).…”
Section: Chlamydiaementioning
confidence: 99%
“…Moreover, the C. trachomatis inclusion membrane protein IncD specifically interacts with the PH (pleckstrin homology) domain of CERT, suggesting that IncD is involved in the recruitment of CERT to C. trachomatis inclusions. Co-transfection studies together with phylogenetic analysis revealed that both the N- and C-terminal regions of IncD are required for binding to the CERT PH domain, allowing C. trachomatis to redirect host cell-derived ceramides to inclusions more efficiently ( Kumagai et al, 2018 ). In cells depleted of CERT ( via short interfering RNAs and siRNAs), CERT was no longer detected on the surfaces of C. trachomatis inclusions, which resulted in smaller inclusions than cells treated with control siRNAs ( Derre et al, 2011 ; Elwell et al, 2011 ).…”
Section: Chlamydiaementioning
confidence: 99%
“…When cells are infected with Chlamydia trachomatis , an obligate intracellular bacterium, CERT is hijacked by the bacterial protein IncD to deliver the host‐derived ceramide to the pathogen . PtdIns 4‐kinase IIα is also hijacked by C. trachomatis to modulate host trafficking by generating a PtdIns(4) pool in the inclusion membrane.…”
Section: Conclusion and Possible Future Perspectivesmentioning
confidence: 99%
“…In addition, CERT is required for the proliferation of several Chlamydia species ( C. trachomatis , C. muridarum , and C. psittaci ). CERT is recruited to the inclusion membrane by binding to the inclusion membrane protein IncD , which is encoded by the C. trachomatis genome. In Chlamydia ‐infected cells, the Golgi apparatus is fragmented, and the resultant Golgi mini‐stacks are scattered around the inclusions .…”
mentioning
confidence: 99%